A dry ligand-binding cavity in a solvated protein - Qvist, Johan (National Academy of Sciences, 2008)
Ligands usually bind to proteins by displacing water from the binding site. The affinity and kinetics of binding therefore depend on the hydration characteristics of the site. Here, we show that the extreme case of a completely dehydrated free binding site is realized for the large nonpolar binding cavity in bovine β-lactoglobulin. Because spatially delocalized water molecules may escape detection by x-ray diffraction, we use water (17)O and (2)H magnetic relaxation dispersion (MRD), (13)C NMR spectroscopy, molecular dynamics simulations, and free energy calculations to establish the absence of water from the binding cavity. Whereas carbon nanotubes of the same diameter are filled by a hydrogen-bonded water chain, the MRD data show that the binding pore in the apo protein is either empty or contains water molecules with subnanosecond residence times. However, the latter possibility is ruled out by the computed hydration free energies, so we conclude that the 315 Å(3) binding pore is completely empty. The apo protein is thus poised for efficient binding of fatty acids and other nonpolar ligands. The qualitatively different hydration of the β-lactoglobulin pore and carbon nanotubes is caused by subtle differences in water–wall interactions and water entropy.